DNA metabarcoding reveals vertical variation and hidden diversity of Alveolata and Rhizaria communities in the western North Pacific. (May 2022) - Sogawa, Sayaka; Nakamura, Yasuhide; Nagai, Satoshi; Nishi, Noriko; Hidaka, Kiyotaka; Shimizu, Yugo; Setou, Takashi
Abstract: Metabarcoding technology using high-throughput sequencing has revolutionized the current understanding of the diversity and ecology of eukaryotic microorganisms. The aim of the present study was to investigate vertical and seasonal variation in eukaryotic plankton communities and to assess the diversity of eukaryotic plankton, using 18S rRNA sequencing, over a depth gradient in subtropical waters affected by the Kuroshio Current. In particular, the present study focused on the diversity and ecology of Alveolata and Rhizaria taxa, which include a variety of plankton species with fragile skeletons or soft bodies. Three vertically distinct eukaryotic communities were identified: the Kuroshio-influenced epipelagic zone (<200 m), the North Pacific Intermediate Water (NPIW)-dominated mesopelagic zone (500–1000 m), and the bathypelagic zone (2000–3000 m). The operational taxonomic unit (OTU) richness was greatest near the surface (<200 m depth), gradually decreasing with increasing depth, and lowest in deeper layers, and OTU diversity (Pielou's evenness and Shannon-Wiener diversity indices) were lowest in the mesopelagic layer (500–1000 m depth). Hidden diversity was observed in both groups in both the surface and deeper layers of the western North Pacific, as well as in the NPIW, which was characterized by the lowest salinity and oxygen concentrations in the study area. In the NPIW, the Rhizaria yielded relatively more sequence reads than other taxa. Furthermore, specific taxa, such as Collodaria (Radiolaria), Syndiniales (dinoflagellates), and Oligohymenophorea (ciliates), were predominant, according to OTU richness and the relative abundance of sequence reads. These findings indicate that a unique ecosystem was formed over time in the NPIW-isolated water mass. Highlights: Eukaryotic community zoned vertically, Kuroshio epi-, NPIW meso- and bathypelagic. Eukaryotic plankton diversity was remarkably low in the NPIW. Collodaria, Syndiniales and Oligohymenophorea were predominant in the NPIW. Acantharia, Nassellaria, Spumellaria and Phaeodaria OTUs peaked at 100 m depth. Taxopodia, Nassellaria and "Other Cercozoa" reads peaked in the deepest layer.